Influence maximization by probing partial communities in dynamic online social networks. Issue 4 (28th June 2016) - Han, Meng; Yan, Mingyuan; Cai, Zhipeng; Li, Yingshu; Cai, Xingquan; Yu, Jiguo
Abstract: With the rapid development of online social networks, exploring influence maximization for product publicity and advertisement marketing has attracted strong interests from both academia and industry. However, because of the continuous change of network topology, updating the variation of an entire network moment by moment is resource intensive and often insurmountable. On the other hand, the classical influence maximization models Independent Cascade and Linear Threshold together with their derived varieties are all computationally intensive. Thus, developing a solution for dynamic networks with lower cost and higher accuracy is in an urgent necessity. In this paper, a practical framework is proposed by only probing partial communities to explore the real changes of a network. Our framework minimizes the possible difference between the observed topology and the real network through several representative communities. Based on the framework, an algorithm that takes full advantage of our divide‐and‐conquer strategy, which reduces the computational overhead, is proposed. The systemically theoretical analysis shows that the proposed effective algorithm could achieve provable approximation guarantees. Empirical studies on synthetic and real large‐scale social networks demonstrate that our framework has better practicality compared with most existing works and provides a regulatory mechanism for enhancing influence maximization. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, a practical framework is proposed by only probing partial communities to explore the real changes of a dynamic network. Our framework minimizes the possible difference between the observed topology and the real network through several representative communities. Based on the framework, an algorithm that takes full advantage of our divide‐and‐conquer strategy, which reduces the computational overhead, is proposed. The systemically theoretical analysis shows that the proposed effective algorithm could achieve provable approximation guarantees.